Letters from Jan čEp to Josef Tichý (an Edition with an Introduction to the Correspondence) - Komendová, Tereza (Bohemica Olomucensia, 2024)
This study provides the reader with the correspondence of Jan Čep to Josef Tichý, the editor of the Olomouc publishing house Velehrad and Čep's friend. The correspondence contains thirty-one letters and eight postcards sent by Jan Čep to Josef Tichý from 1939 to the end of 1947. The letters (together with Josef Tichý's memoirs of one of his visits to Myslechovice) are kept in the Memorial of Literature in Moravia in Rajhrad.
Keywords: Jan Čep; Josef Tichý; publishing house Velehrad; redactor; edition; correspondence